Growth Laws for the Phase-ordering Dynamics of the B1 Phase of a Bent-core Liquid Crystal - CHAN, HO-KEI (My University, 2004)
We have experimentally investigated the dynamics of the phase ordering process of bent-core molecules at isothermal conditions, forming the liquid crystalline ?banana? B1 phase from the isotropic melt. In contrast to the fractal growth patterns observed for other ?banana? liquid crystal phases, the B1 phase exhibits dendritic-like growth, which at short times shows similar growth structures as observed for conventional smectic batonnet growth. Analysis with respect to growth laws of the form L(t)~tn shows that the growth process follows the theoretically predicted Allen-Cahn dynamics with n=1?2 for zero difference in the free energy between the high- and the low-temperature phase, while the growth exponent approaches n?1 for increasing supercooling. From the experimentally obtained data, we estimate the ratio between volume and curvature driven contributions to the phase ordering process as a function of supercooling and suggest a phenomenologically determined relationship of log ?F~?T for the difference in free energy between the high- and the low-temperature phase as the quench depth is varied.
PUBLISHED
This paper presents experimental evidence that, for the nucleation and growth of liquid crystal phases upon supercooling, the same set of growth laws are universally obeyed irrespective of molecular details nor the shape of the growing domain.
Keywords: Physics